A Spatially Varying Scaling Method for InSAR Tropospheric Corrections Using a High‐Resolution Weather Model. Issue 4 (5th April 2019) - Shen, Lin; Hooper, Andrew; Elliott, John
Abstract: Variation in tropospheric delay is a major limiting factor on the accuracy of interferometric synthetic aperture radar (InSAR) measurements. This is particularly the case when deformation and topography are correlated. To address limitations of previous InSAR tropospheric correction methods, here we present a new approach that combines the use of both external weather model data and the interferometric phase. We assume that vertical refractivity profiles calculated from a high‐resolution weather model data can generally describe the form of the relationship between tropospheric delay and height but that the magnitude can be incorrect. We estimate a magnitude correction by scaling the original delays to best match the interferometric phase. We validated our new method using simulated data and demonstrate that both coseismic and interseismic signals can be separated from strong tropospheric delays. We also applied our algorithm to the central portion of the Altyn Tagh Fault in northern Tibet, where deformation correlates strongly with topographic relief of 6, 000 m, and show that the derived velocity field is more internally consistent and agrees better with independent Global Positioning System measurements. Key Points: We present a new empirical method for InSAR tropospheric corrections using high‐resolution weather model products A spatially varying scaling factor is used to refine the magnitude of tropospheric delays We improve the isolation of the deformation signal across the Altyn Tagh Fault zone, which spans 6, 000 m of topographic relief